Assessing Physical Therapists’ Expectations and Experiences With an Automated Rehabilitation System Using Technology Acceptance Model: Multiple Methods Pilot Study - Cynthia Williams; Lindsay Toth; Raine Osborne; Chloe E Bailey; Aishwarya Joshi (JMIR Rehabilitation and Assistive Technologies)
Abstract BackgroundWearable sensor systems maximize visual and clinical feedback for physical therapists to enhance patient outcomes in rehabilitation medicine. However, physical therapists must adopt and accept new technologies for full integration into routine care to advance the use of technology in clinical care. Their role in technology design is critical in adopting and implementing technology. Interprofessional collaboration should be supported in the design of rehabilitation-assisted technologies. ObjectiveWe used the established tenets of the Technology Acceptance Model to describe physical therapists’ expectations and experiences before and after using a novel wearable system in outpatient physical therapy. MethodsThis multiple methods pilot study used a comparative pre-post survey and a qualitative semistructured focus group study design. Using purposive sampling, we recruited outpatient physical therapists to pilot the novel wearable technology, describe their expectations and experiences, and participate in a semistructured focus group discussion conducted to gather training and user experience information. ResultsThe study sample consisted of 5 physical therapists with an average age of 38.8 (SD 6.9) years and a work experience average of 12 (SD 7.7) years. Presurvey data show favorable expectations for usefulness and ease of use; however, favorability in both factors decreased after use. For perceived usefulness, all responses moved in the less favorable direction; mean difference −4.4 (SD 3.21); PPP ConclusionsThe Technology Acceptance Model–based survey responses and focus group themes outcomes demonstrated that physical therapists’ expectations for using new technology were not met. Engaging physical therapists in piloting novel wearable technology highlights the importance of physical therapist engagement in developing, refining, and implementing wearable devices for rehabilitation.